Sex Differences in Reliability of Tests to Assess Cognitive Function - Vaida Berneckė; Kazimieras Pukėnas; Marius Brazaitis (Lithuanian Sports University, 2018)
Background. The purpose of this study was to identify whether the learning effect, fatigue, motivation, effort and/or sex-specific neural, physiological and morphological factors influenced the results of the test-retest reliability of tests to assess cognitive function. Methods. The  sample  included  ten  men  (age  21.2  ±  0.4  years;  body  mass  79.5  ±  8.3  kg)  and  ten  women (age 22.0 ± 1 years; body mass 60.0 ± 10.0 kg). Participants accomplished six tests (three for memory and three for attention) four times, i.e. two times (with 24 hours' break) on successive days (teaching) and two times (with 48 hours' break) on the third and fifth days (re-testing to assess the reliability). The reliability was assessed by calculating the average of the population, standard deviation, and intraclass correlation coefficient (ICC).   Results. In males and females, measurements of attention function were highly reliable over time (ICC > .84). The ICCs for volume of spatial memory were above .79, for memory of even number recognition above .57 for both genders and for memory of figure recognition .00 for males and .79 for females. Conclusion. In young healthy males and females, measurements of attention function were highly reliable over time. Meanwhile, reliability for volume of spatial memory was good/high for both sexes, but reliability of  memory  for  even  number  recognition  was  insufficient  for  both  sexes  and  results  from  memory  of  figure recognition showed good reliability for women and insufficient reliability for men. Keywords:  memory, attention, test-retest, reproducibility, gender.